Emotions, COVID-19 related thoughts and satisfaction with life during the critical period from control to relaxation - Diao, Chunting; Tan, Huiping; Wen, Yanhui; Zhu, Ruiyue; Wu, Xiaoyue; Zhang, Shiqi; Zhao, Yongzhi; Liu, Nian; Zhou, Xuan; Hu, Zhen (Frontiers in Psychology, 2023)
Introduction In the context of declining mortality rates and increasing infectivity, it has become unavoidable for the majority of individuals to experience a COVID-19 infection at some point. This study aimed to investigate the psychological well-being of the general population during China’s transition period from strict control measures to relaxed policies in COVID-19 prevention and control, as well as the impact of COVID-19 related thoughts on emotion and life satisfaction during widespread infections. Methods A cross-sectional study was conducted involving a sample size of 1578 participants. Participants completed self-report questionnaires assessing positive and negative emotions, thoughts about COVID-19, and satisfaction with life. Demographic characteristics such as sex, age, and education level were controlled for in the analysis. Results The findings revealed that individuals who had been infected with COVID-19 (specifically the Omicron variant BA.5.2 or BF.7) reported lower levels of positive emotions compared to those who were uninfected or had recovered from the infection. There was a significant relationship between COVID-19-related thoughts, emotions, and life satisfaction. Positive COVID-19 related thoughts were found to mediate the relationship between negative emotions and satisfaction with life. Discussion This study represents a comprehensive examination conducted in China, focusing on assessing the impact of the COVID-19 pandemic on the general population during the critical transition period from control to relaxation. Throughout this period, the number of infections experienced fluctuations, initially rising but eventually declining over a one-month span. In such a momentous historical period, maintaining a positive perspective on COVID-19 and its management becomes paramount in enhancing the emotional well-being, life satisfaction and overall well-being of individuals.